Topological Design and Kinematic Performance Analysis of a New Parallel Mechanism with Two Translations and Two Rotations - Ji Encheng; Shen Huiping; Li Ju (Jixie chuandong)
Firstly, based on the topological structure design method of the parallel mechanism, a two-translation and two-rotation (2T2R) parallel mechanism is designed. Its coupling degree is 1, and the position orientation characteristics （POC） set, constraint degree and degree of freedom are calculated. Secondly, the topological characteristic kinematics of the mechanism is analyzed, and the forward and inverse position solutions of the mechanism are solved, which verifies the correctness of the forward and inverse solutions. Finally, based on the inverse position solution, the singularity and workspace of the mechanism are analyzed and calculated, the possible singular position of the mechanism is obtained, and the maximum reachable space of the mechanism is obtained, which lay a foundation for the dynamics and dynamic balance research of the mechanism, as well as the manufacturing of the prototype.